Analysis of Loess Wet Deformation and Slope Stability under Rainfall Conditions. Issue 1 (May 2021) - Zhou, Heng; Di, Shengjie; Zhang, Ying
Abstract: Loess is a typical unsaturated soil, and the unsaturated strength is the basis for the analysis and evaluation of engineering stability in the loess area. Based on the analysis of the wet load deformation strength, rainwater infiltration and slope stability of unsaturated loess, this paper obtains the yield stress under different suction caused by soil humidification at different depths, the water retention characteristic curve and the different loess with different dry-wet cycle history. The research conclusions can provide reference for the construction of loess collapsibility model and the numerical calculation of the collapsibility deformation of the loess site under the infiltration of rainwater.